Aktifitas Antifungi Ekstrak Etanol Kulit Buah Jeruk Siam Terhadap Phytophthora sp. Im5 dari Pangkal Batang Tanaman Jeruk Siam (Citrus nobilis var. microcarpa) - Mukarlina, Khusnul Khotimah, Rahmawati (Jurnal Protobiont, 2017)
Basal stem rot is one of the diseases in siamese citrus (Citrus nobilis var. microcarpa) wich is caused by fungi Phytophthora sp. Im5. Phytophthora sp. Im5 growth can be inhibited by utilizing natural antifungi compounds deried from plant extracts. One of the plants that has potential to be antifungi is siamese citrus peel. This research aimed to find out the effect of ethanol extract in siamese citrus peel on inhibiting the growth of fungi Phytophthora sp. Im5. This research was conducted for 2 months from March to April 2017 in Microbiology Lab of Mathematics an Natural Science Faculty Tanjungpura University and in Plantation Processing Laboratory of State Polytechnic Pontianak. The research used completely randomized design with 4 treatments, namely control, siamese citrus extract 0,55 g/ml, 0,65 g/ml and 0,75 g/ml. The results show that the inhibition of the growth of fungi Phytophthora sp. Im5 with concentration of ethanol extract of 0,55 g/ml, 0,65 g/ml and 0,75 g/ml was not significantly different between treatments, but significantly different from control. A concentration of 0,55 g/ml is the best concentration to inhibit the growth of fungi Phytophthtora sp. Im5 with a percentage of inhibitory power of 78,41% and the activity level was very strong.